Religion in Europe: contemporary perspectives - Gill, Sean; D'Costa, Gavin; King, Ursula (Kok Pharos, 1994)
Judaism in Europe / Jonathan Gorsky -- Christianity in Europe / Duncan Forrester -- Islam in Europe / Peter Antes -- Hinduism and Hindus in Europe / Rohit Barot -- Buddhism and European culture in Europe / Stephen Batchelor -- Sikhs in Europe / Owen Cole -- New religious movements in Europe / Eileen Barker -- Women in the churches of Europe / Mary Grey -- Religion and socialism / David McLellan -- Religion and nationalism / John Kent -- Christian churches and political change in Eastern Europe / Michael Pye -- Interfaith developments in Europe / Marcus Braybrooke